Sistem Pakar Diagnosis Penyakit Penyebab Abortus Pada Ibu Hamil Menggunakan Metode Certainty Factor Berbasis-Web - Adebunda Jessica; Yoseph Pius Kurniawan Kelen; Hevi Herlina Ullu (Riau Jurnal Teknik Informatika, 2026)
Abortion can be caused by various diseases and are often not recognized at an early stage, posing serious risks to both pregnant women and their fetuses. Limited public knowledge about the early symptoms of abortion may delay apropriate medical treatment. This study aims to develop a web-based expert system to support the early consultation and diagnosis of abortion in pregnant women. The system applies the certainty factor (CF) method to calculate the confidance level of the diagnosis based on the symptoms selected by the user and the confidance values provided by medical expert. The knowledge base consists of disease data, symptoms data, Measure of belief (MB) and Measure of Disbelief (MD) values, as well as diagnostic rules obtained through expert interviews and literature review. The results show that the proposed system is capable of permorming the diagnistic process and presenting the confidance percentage for the identified disease. Funcional testing using the Black Box Testing method confirmed that all system features operated as intended. Furthmore, validation using 50 test cases compared with expert diagnoses achieved an accuracy rate of 90%. These findings indicate that the Certainty Factor method can produce diagnostic result that closely match expert judgments, making the system suitable as an initial consultation tool to assist in identifying deseases that may cause abortion in pregnant women.